Empirical Analysis of Factors Affecting Export Performance at Tanjung Emas Port, Semarang, Indonesia - Rahmasari, Lisda (LifeSciFi, 2023)
The development of the world of trade in the era of globalization has made the boundaries of trade flows increasingly free. In order to maintain the stability of the export value, various improvements need to be made in the export activity sector itself. The aim of this research is to analyze the influence of government policy, implementation of logistics systems and export product quality on export performance at Tanjung Emas Port, Semarang. This research uses quantitative methods with the number of samples used being 124 respondents consisting of employees of trading manufacturing companies that carry out export activities at the Tanjung Emas Port, Semarang. The independent variables analyzed in this research are government policy, implementation of the logistics system, and quality of export products. Meanwhile, the dependent variable is export performance at Tanjung Emas Port, Semarang. Next, the data was analyzed using SPSS software. The research results show that government policy has a positive effect on export performance. The implementation of a logistics system has a positive effect on export performance. Lastly, export products have a positive effect on export performance.